Proceedings of IEEE/RSJ International Conference on Intelligent Robots and Systems (IROS'94)
DOI: 10.1109/iros.1994.407584
|View full text |Cite
|
Sign up to set email alerts
|

WISEKO: a knowledge-based system for the recognition of 2D-complex objects in CAQ applications

Abstract: The automatical recognition of complex objects ( objects with one or more drills) represents a central scope of duties in the automatization of numerous production processes. Contrary to simple objects ( objects without drills) which outer contour form represents the single recognition feature, for complex objects further features must be determined and connected with each other to describe these objects.For the recognition of workpieces for example additional to the outer contour form of the workpiece, the nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…The first method describes the object outlines and the second describes the object areas. Suitable contour and region primitives are first used in order to extract the relevant objects from a given image (e.g., Freeman codes [18], polygon lines [19], and pixels or image squares [20]). Based on this data, shape description can be performed by applying a feature vector in order to represent the given objects.…”
Section: Existing Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first method describes the object outlines and the second describes the object areas. Suitable contour and region primitives are first used in order to extract the relevant objects from a given image (e.g., Freeman codes [18], polygon lines [19], and pixels or image squares [20]). Based on this data, shape description can be performed by applying a feature vector in order to represent the given objects.…”
Section: Existing Methodsmentioning
confidence: 99%
“…Precision is given by (18) Recall is given by (19) Accuracy (20) Where is the number of images retrieved in the top N positions that are similar to the query image and M is the total number of images in the database similar to the query image. Table 1 shows the comparison results of Proposed Method with Texels of Fuzzy Textons (TFT) [21] and TT [29].…”
Section: Performance Measurementioning
confidence: 99%
“…To derive an angle function, we use the polygon information of a given object shape derived after contour extraction and approximation [10]. Figure 1 shows the example of an object shape with five edges; its derived angle (green colored) and the periodical angle function * (blue colored) are shown in Figure 2.…”
Section: Shape Description Using An Angle Functionmentioning
confidence: 99%
“…In recent years, many methods for shape representation and recognition have been proposed [1][2][3][4][5][6][7][8][9][10]. An advanced review of shape representation techniques can be found in [1,2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation